The Effect of Using Different Restoration Techniques on the Fracture Resistance of Anterior Endodontically Treated Teeth with Class III Cavities (In Vitro Study (Journal of Hama University, 2022)
• Studying the effect of using glass fiber posts on the fracture resistance of anterior endodontically treated teeth with Class III Cavities.• Studying the effect of using full ceramic crowns on the fracture resistance of anterior endodontically treated teeth with Class III Cavities.40 human maxillary centrals were extracted due to periodontal reasons, then they were endodontically treated. Standardized Class III cavity preparations were made on the mesial and distal surfaces. The final horizontal size of the Class III preparations corresponded to 1/4 of the mesiodistal dimension, and the vertical size corresponded to 1/3 of the cervicoincisal dimension.The specimens were divided randomly into Four groups according to the treatment method.Group A (glass fiber Posts and full ceramic crowns), Group B (composite and full ceramic crowns), Group C (glass fiber posts and composite) and Group D (just Composite). All teeth were subjected to a universal testing machine. Statistical analysis was performed on data with One-Way ANOVA.there were no statistically significant differences between the four groups.• there was no effect of using glass fiber posts on the fracture resistance of anterior endodontically treated teeth with class III cavities.• there was no effect of using full ceramic crowns on the fracture resistance of anterior endodontically treated